2017
DOI: 10.2340/00015555-2556
|View full text |Cite
|
Sign up to set email alerts
|

Two Annular Alopecic Lesions on the Scalp in a Young Asian Man: A Quiz

Abstract: This is an open access article under the CC BY-NC license. www.medicaljournals.se/acta

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…Among patients with lupus panniculitis, 5 presented linear alopecia. 8,22,27,28,30 Follicular plugging was noted in four cases (our case and previous studies), 14,29,35 sclerosis in three 13,19,35 and milia in one. 25 Patients were mostly asymptomatic but pruritis was occasionally noted.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Among patients with lupus panniculitis, 5 presented linear alopecia. 8,22,27,28,30 Follicular plugging was noted in four cases (our case and previous studies), 14,29,35 sclerosis in three 13,19,35 and milia in one. 25 Patients were mostly asymptomatic but pruritis was occasionally noted.…”
Section: Discussionsupporting
confidence: 76%
“…3,8 13 1 1 (100) --AZA c, 15 1 1 (100) --Antimalarial and dapsone b,c, 31 1 1 (100) --2. Antimalarial with 19 12 (63) 6 (32) 1 (5) In monotherapy 10,11,23,26 4 3 (75) 1 (25) -Topical corticosteroids 8,14,19,28,35 5 4 (80) 1 (20) -TCI (our case and previous studies) 3 4 -4 (100) -Topical corticosteroids and TCI (our case and previous studies) 34 6 1 1 (100) --Topical anti-inflammatory 6 1 1 (100) --Topical corticosteroids 12 1 1 (100) --Systemic corticosteroids and antimalarial b,c, 31 Multiple treatments have been described with pediatric LCLE (Table 1). 3,[6][7][8][9][10][11][12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][28][29][30][31][32]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The differential diagnoses with clinical and dermoscopic examination of the linear non-scarring alopecia, including alopecia areata, trichotillomania, and traction alopecia, could importantly yield explicit data for better diagnosis. Hair loss could be presented in alopecia areata, with a band-like distribution along the hairline, 24 mostly shown as dermoscopic yellow dots, black dots, and exclamation mark hair. 25 Although the bizarre-shaped patches of hair loss was usually found in trichotillomania, with the multiple dermoscopic broken hair shaft abnormalities such as flame-shaped and tulip hair sign without significant inflammation or changes in the perifollicular area.…”
Section: Discussionmentioning
confidence: 99%
“…Classic lupus panniculitis/lupus profundus are rarer forms of scarring alopecia specific to lupus [48]. Cases of lupus panniculitis have shown positive responses and complete resolution in some patients with HCQ treatment [48][49][50][51][52][53][54][55][56][57]. A retrospective cohort study found 66.7% of discoid lupus erythematosus patients responding to HCQ [20].…”
Section: Lupus Alopeciamentioning
confidence: 99%